Selectivity of Molecularly Imprinted Polymer-based Chitosan Membrane for Caffeine Separation by Filtration - Amanda, Eviomitta Rizki; Oktavianti, Lia Wanda; Aisyah, Mareta Nur; Azizah, Cindy Izatin; Nurfadlilah, Lilik (Universitas Andalas, 2025)
Caffeine is a chemical compound that can be isolated from coffee beans. The isolation and purification of caffeine compounds have been successfully carried out using a filtration method using chitosan biomaterial synthesized by molecularly imprinted polymer (MIP). Chitosan as a functional polymer is dissolved in acetic acid (2% v/v) with stirring at 60°C overnight until a clear and homogeneous solution is formed. Furthermore, caffeine as a template molecule is added to the polymer solution and stirred for 60 minutes. The polymer solution is poured into a petri dish until evenly distributed and dried in an oven at 60°C for 12 hours. The dried polymer solution is then soaked in sodium tripolyphosphate as a crosslinking solution and dried again in the oven until the membrane sheet separates from the petri dish. The membrane sheet is then washed using distilled water until the pH is neutral and continued washing with chloroform to remove caffeine from the membrane pores to form an MIP membrane. The formed MIP membrane is characterized using FTIR and SEM. The MIP membrane was then cut into a circle, inserted into an empty syringe, and used to filter samples containing caffeine. The filtration results were analyzed using a UV-Vis spectrophotometer which showed that caffeine filtered with the MIP membrane contained less interference than caffeine filtered with a non-imprinted polymer membrane (NIP). Quantitative analysis was also carried out using the spiked sample method to determine the recovery value of the filtration results. From this study, the percentage recovery value (% recovery) was obtained at 96.16 - 103.80%.